Primary Intradural Extramedullary Spinal Melanoma in the Lower Thoracic Spine. (5th April 2016) - Hering, Kathrin; Bresch, Anke; Lobsien, Donald; Mueller, Wolf; Kortmann, Rolf-Dieter; Seidel, Clemens
Abstract : Background Context. Up to date, only four cases of primary intradural extramedullary spinal cord melanoma (PIEM) have been reported. No previous reports have described a case of PIEM located in the lower thoracic spine with long-term follow-up. Purpose . Demonstrating an unusual, extremely rare case of melanoma manifestation. Study Design . Case report. Methods . We report a case of a 57-year-old female suffering from increasing lower extremity pain, left-sided paresis, and paraesthesia due to spinal cord compression caused by PIEM in the lower thoracic spine. Results . Extensive investigation excluded other possible primary melanoma sites and metastases. For spinal cord decompression, the tumor at level T12 was resected, yet incompletely. Adjuvant radiotherapy was administered two weeks after surgery. The patient was recurrence-free at 104 weeks after radiotherapy but presents with unchanged neurological symptoms. Conclusion . Primary intradural extramedullary melanoma (PIEM) is extremely rare and its clinical course is unpredictable.